(untitled) - Kremenova, Iveta; Fabus, Juraj; Batka, Miroslav (Doprava a spoje, 2005)
The main objective of every university should be to prepare quality graduates, who are prepared and well-educated to be successful in their future work experience. This article deals with survey results done by the Department of Communications staff. The survey is focused on future opportunities of university graduates in the field of Postal and Telecommunication operation. Within this article we also suggest the work possibilities for graduates of new accredited study programmes entitled Postal technology and Postal service.